Effects of blood flow restrictiontraining on muscle function and balance in chronic ankle instability: a systematic review - Wen, Ziliang; Zheng, Bing; Zhu, Jiang; Wu, Xuelian; Wu, Zonghui (Frontiers in Physiology, 2025)
BackgroundChronic ankle instability (CAI) impairs peri-ankle strength and balance. While blood flow restriction training (BFRT) enhances muscle strength, hypertrophy, and activation, its efficacy in CAI remains uncertain, warranting this systematic review.MethodsThis systematic review analyzed randomized controlled trials with BFRT interventions from five databases (PubMed, Scopus, Web of Science, EBSCOhost, CNKI). Relevant data were extracted, and the PEDro Scale was used to assess the methodological quality of each study.ResultsNine studies from four countries were included, involving a total of 263 patients, with publication dates ranging from 2020 to 2024. The PEDro scores of these studies ranged from 6 to 10. Two of the studies demonstrated positive effects on muscle hypertrophy, five showed significant improvements in muscle strength, and four reported enhanced muscle group activation, although there were variations in the activation of specific muscle groups. Of the seven studies assessing balance, one failed to confirm a positive effect.ConclusionThis systematic review demonstrates that blood flow restriction therapy (BFRT) combined with low-intensity conventional rehabilitation training significantly enhances ankle muscle strength and promotes muscle hypertrophy in patients with chronic ankle instability (CAI). Despite variations in training protocols and BFRT parameters across studies, these benefits have been consistently observed in both acute (single-treatment) and short-term (4–6 weeks) interventions. Additionally, most of the included studies underscore the beneficial effects of BFRT on improving muscle activation and balance. However, some of the research results are still inconsistent and require further study.Systematic Review Registrationhttp://inplasy.com, identifier: INPLASY202490117.